Strengthening National Immunization Technical Advisory Groups: Twelve Years of Progress (2012–2023) - Louise Henaff; Laure Dumolard; Vinod Bura; Gerald Etapelong Sume; Sidy Ndiaye; Jennifer Sanwogou; Heeyoun Cho; Joachim Hombach; Christoph A. Steffen (Vaccines)
Introduction: Well-functioning National Immunization Technical Advisory Groups (NITAGs) are valuable contributors to decision-making processes in the complex immunization policy arena. This paper describes the progress made globally on the establishment and strengthening of these key advisory groups and discusses some of their strengths, challenges, and opportunities. Methods: The data submitted annually by countries to the World Health Organization (WHO) via the WHO/UNICEF Joint Reporting Form (JRF) were analyzed, comparing the NITAG functionality criteria in 2012 and 2023. Results: In 2023 and 2012, 88% and 61% of countries, respectively, reported having a NITAG. A total of 77% of NITAGs met all six NITAG process criteria in 2023 compared to 33% in 2012. This progress was most notable in the WHO African Region, increasing from 7% (2012) to 77% (2023), and the South-East Asia Region, increasing from 45% (2012) to 91% (2023). In 2023, 84% of NITAGs issued a vaccine-policy recommendation that was adopted by decision-makers. Discussion: Marked progress has been made since 2012 on establishing and maintaining NITAGs, with a small number of countries yet to form an advisory committee. Supporting and sustaining NITAG functions remains an important means for countries to foster independent and transparent expert advice on vaccine and immunization policy. Setbacks in countries facing instability or political turmoil are a reminder of the reversibility of progress. WHO and partners play an important role in supporting countries in strengthening these advisory committees. Continuous commitment by countries to the function and involvement of NITAGs in policy recommendations is essential for enhancing the strength and resilience of immunization programs.